The Impact of 3D Imaging on Orthodontic Diagnosis and Treatment Planning: A Systematic Literature Review - Yadav, Anju; Gupta, Jatin; Rukshana, Rashmi; Yadav, Vishaka; Kumari, Khushbu; Jyotsana, Jyotsana (Journal of Neonatal Surgery, 2025)
The introduction of three-dimensional (3D) imaging in orthodontics has significantly transformed diagnosis, treatment planning, and patient care. Traditional two-dimensional (2D) imaging techniques, such as X-rays and cephalometric radiographs, provide limited insight into the complex 3D structures of the craniofacial region. Recent advancements in 3D imaging technologies like Cone Beam Computed Tomography (CBCT), 3D facial scanning, and digital models have provided more accurate and detailed visualizations, leading to improved orthodontic practices. Objective This systematic literature review aims to evaluate the applications, advantages, limitations, and clinical impacts of 3D imaging technologies in orthodontics. The review synthesizes findings from multiple studies to provide an in-depth analysis of the role of 3D imaging in enhancing diagnostic accuracy and treatment planning. Methods A comprehensive search of peer-reviewed articles was conducted using databases such as PubMed, Scopus, and Web of Science. The inclusion criteria focused on clinical trials, observational studies, and systematic reviews published between 2000 and 2024, involving human subjects and discussing 3D imaging in orthodontic applications. A total of 8 studies were selected for inclusion based on relevance and quality. Results The review highlights the significant benefits of 3D imaging, including improved diagnostic precision, detailed visualization of craniofacial structures, and more accurate treatment planning. CBCT has become particularly valuable in diagnosing complex cases, while 3D facial scanning and digital models have enhanced clear aligner therapy. Despite these advancements, challenges remain, including the high cost of equipment, radiation exposure concerns, and the need for specialized software and training. Conclusion 3D imaging technologies have revolutionized orthodontics, offering enhanced diagnostic tools, better treatment outcomes, and personalized care. However, barriers to widespread adoption, such as cost and radiation exposure, need to be addressed. Future research should focus on optimizing these technologies for broader accessibility and improving patient safety.